Role of GFI1 in Epigenetic Regulation of MDS and AML Pathogenesis: Mechanisms and Therapeutic Implications - Möröy, Tarik; Khandanpour, Cyrus (Frontiers in Oncology, 2019)
Growth factor independence 1 (GFI1) is a DNA binding zinc finger protein, which can mediate transcriptional repression mainly by recruiting histone-modifying enzymes to its target genes. GFI1 plays important roles in hematopoiesis, in particular by regulating both the function of hematopoietic stem- and precursor cells and differentiation along myeloid and lymphoid lineages. In recent years, a number of publications have provided evidence that GFI1 is involved in the pathogenesis of acute myeloid leukemia (AML), its proposed precursor, myelodysplastic syndrome (MDS), and possibly also in the progression from MDS to AML. For instance, expression levels of the GFI1 gene correlate with patient survival and treatment response in both AML and MDS and can influence disease progression and maintenance in experimental animal models. Also, a non-synonymous single nucleotide polymorphism (SNP) of GFI1, GFI1-36N, which encodes a variant GFI1 protein with a decreased efficiency to act as a transcriptional repressor, was found to be a prognostic factor for the development of AML and MDS. Both the GFI1-36N variant as well as reduced expression of the GFI1 gene lead to genome-wide epigenetic changes at sites where GFI1 occupies target gene promoters and enhancers. These epigenetic changes alter the response of leukemic cells to epigenetic drugs such as HDAC- or HAT inhibitors, indicating that GFI1 expression levels and genetic variants of GFI1 are of clinical relevance. Based on these and other findings, specific therapeutic approaches have been proposed to treat AML by targeting some of the epigenetic changes that occur as a consequence of GFI1 expression. Here, we will review the well-known role of Gfi1 as a transcription factor and describe the more recently discovered functions of GFI1 that are independent of DNA binding and how these might affect disease progression and the choice of epigenetic drugs for therapeutic regimens of AML and MDS.